Makna Teologi Mapepegat Dalam Upacara Ngaben Di Desa Tengkudak, Kecamatan Penebel, Kabupaten Tabanan - I Ketut Gunarta (Jurnal Penelitian Agama Hindu, 2020)
Mapepegat in the Ngaben ceremony is a form of yajna implementation aimed at Ida Sang Hyang Widhi Wasa and its manifestations with the aim that the Atma can run smoothly towards the creator, and ask that in this life and life not be bound by worldly elements. The Mapepegat ceremony carried out by the people of Tengkudak Village still has imbalances in its implementation in terms of time and place of implementation and is not very well known by the community at large. This research raises a problem, namely about the theological meaning of the mapepegat ceremony in the Ngaben ceremony held in Tengkudak Village. To analyze this problem, symbol theory is used. The data used in this study are primary and secondary data. Primary data comes from the field or from the place where the research is carried out, while secondary data is data that comes from literature or literature. Data collection was collected by means of observation, interviews, literature and documentation. To analyze the data obtained using descriptive qualitative methods. Mapepegat in this Ngaben ceremony uses the facilities and infrastructure of the ceremony such as the mapepegat banten. The meaning in the mapepegat ceremony is described through several meanings including the meaning of sincerity, the meaning of togetherness, the meaning of harmony and social meaning.